Inventory Analysis of Goods Increasing Sales: a Case in a Distributor Company - Hartono, Hartono; Susanti, Jeli (Institut Ilmu Sosial dan Manajemen STIAMI, 2023)
The phenomenon of this research is the delay in the delivery of goods by PT Wicaksana Overseas International Tbk to consumers (distributors). The purpose of this study is to analyze the application of the inventory forecasting method, the obstacle that occurs in the fulfillment of the stock of goods, and the efforts that need to be made to overcome these obstacles. This research is a descriptive research in which the author collects data through interviews, observation, documentation, and literature study, and describes the results of the research as is according to existing data sources. Sources of data collected for this study included primary data, i.e. results of interviews, and secondary data, i.e. the data obtained from PT Wicaksana Overseas International Tbk. The results of this study are: (1) Inventory forecasting on sales indicates that if sales promotions increase, on average the demand planning team will increase the amount of inventory by about 30% of normal inventory; (2) the company's obstacles in meeting the availability of goods are limited production of goods, especially raw materials, sales promotion plans or promo plans that are not communicated with the company's internal team (demand planning, sales and marketing teams), small warehouse capacity, and outlets' delays in making payments; (3) the company's efforts in dealing with obstacles to the availability of stock of goods is to be re-assured with the client or colleagues about the time required to solve the problem of producing goods, to carry out good coordination between clients or colleagues with the company's internal team, to expand the warehouse area in the Jakarta surroundings, and continue to make financial improvements.